Current Controversies: Are Free Vitamin Metabolite Levels a More Accurate Assessment of Vitamin D Status than Total Levels? - Bikle, Daniel D; Malmstroem, Sofie; Schwartz, Janice (Endocrinology and metabolism clinics of North America, 2017)
The free hormone hypothesis postulates that only the nonbound fraction (the free fraction) of hormones that otherwise circulate in blood bound to their carrier proteins is able to enter cells and exert their biologic effects. For the vitamin D metabolites less than 1% (0.4% for 1,25(OH) D and 0.03% for 25(OH)D) is free, with more than 99% bound to the vitamin D binding protein (DBP) and albumin (approximately 85% and 15%, respectively). Assays to measure the free vitamin D metabolite levels have been developed, and initial studies indicated their value in subjects with altered DBP levels.